Integrated Bacterial and Fungal Microbiome Profiling of Green Honey from Banggi Island, Sabah - Ullah, Saeed; Huyop, Fahrul Zaman (Journal of Tropical Life Science, 2026)
Green honey from Banggi Island, Sabah, is a premium product recognized for its distinctive color, yet its microbial composition remains poorly characterized. This study employed amplicon sequencing to investigate the microbial diversity of green honey, targeting the bacterial 16S rRNA V3 region and the fungal internal transcribed spacer one (ITS1) region. A total of 286 amplicon sequence variants (ASVs) were identified, comprising 270 bacterial and 16 fungal/yeast ASVs across 12 bacterial and 2 fungal phyla. The bacterial community was dominated by members of the phylum Pseudomonadota, with representative genera including Comamonas, Acidovorax, and Bacillus. Fungal profiling revealed a strong dominance of Zygosaccharomyces rouxii, accounting for over 98% of fungal reads. Overall, fungal sequencing reads substantially exceeded bacterial reads, indicating a fungal-enriched microbial profile in this honey sample. These findings provide the first integrated characterization of both bacterial and fungal communities in Banggi Island green honey. While the results highlight distinct microbial patterns potentially shaped by local environmental and floral factors, functional, safety, and bioactivity implications remain exploratory and warrant further investigation using complementary approaches.